Bibliometric analysis of European publications between 2001 and 2016 on concentrations of selected elements in mushrooms - Świsłowski, Paweł; Dołhańczuk-Śródka, Agnieszka; Rajfur, Małgorzata (Environmental science and pollution research international, 2020)
This article presents a bibliometric study of 200 European publications released between 2001 and 2016, about the contamination of mushrooms by selected elements. The analysis includes figures on the type of analyte, its concentration, the species of fungi, and its country of origin. In the literature review, 492 species of mushrooms (wild-growing and cultured) found in 26 European countries and their concentration of 74 associated elements were analysed. The papers, which dealt mainly with the heavy metal (Cd, Cu, Fe, Pb, and Zn) concentrations of mushrooms, primarily came from Turkey, Poland, Spain, and the Czech Republic. More than 50% of the publications provided data about edible mushrooms. The results of the bibliometric analysis showed that over the 16 years, European research on fungal contamination by selected analytes has not lessened in popularity and is ongoing. Many of the studies underlined the need to assess the risk to human health arising from the consumption of contaminated mushrooms taken from various habitats. These results were the effect of, among other things, the strong interest in studies carried out on edible species, in which concentrations of mainly heavy metals that are dangerous to health and are marked were indicated (Cd, Pb, and Hg).
Keywords: Environmental Monitoring; Heavy metals; Mushrooms; Turkey; monitorování životního prostředí; Spain; Review; těžké kovy; bibliometrie; Česká republika; Poland; Europe; Agaricales; látky znečišťující půdu; Soil Pollutants; Czech Republic; Evropa; Turecko; Bibliometric analysis; Bibliometrics; lidé; Humans; Španělsko; Metals, Heavy; Polsko